ANALISIS NILAI TAMBAH BODY SCRUB DARI KULIT CERI KOPI LIBERIKA DI PROVINSI JAMBI - Permata Sari, Fenny (Jurnal Agroindustri Pangan, 2023)
There is a lot of solid waste from the liberika coffee industry, in the form of coffee cherry skin waste which is not utilized further. Liberika coffee cherry skin waste has the potential to be made into a product, namely body scrub. This study aims to (1) determine the body scrub processing (2) analyze added value and (3) analyze the financial feasibility of processing body scrub from Liberika coffee cherry skin. The method used in this research is descriptive and quantitative methods. In analyzing added value, the method used is the Hayami method. The results of this study indicate that the added value generated from the processing of body scrub from Liberika coffee cherry skin is Rp. 210,626/kg of raw material with an added value ratio of 42%. This means that the added value generated is greater than zero (Rp. 210,626> 0), meaning that this business can provide (positive) added value. For financial feasibility analysis, the BEP value for production volume was 39,709 packages/year and the selling price BEP was Rp. 4,792. The resulting NPV is Rp. 218,505,606 (NPV > 0), meaning that this business is feasible to run. The IRR obtained is 53% with a Net B/C of 1.15 and a Payback Period (PP) of 2 years 6 months 18 days. This means that the business of processing body scrub from the skin of Liberika coffee cherries is profitable and feasible to run.